2015
DOI: 10.1371/journal.pone.0127078
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of Susceptibility Genes Triggering Lachrymal/Salivary Gland Lesion Complications in Japanese Patients with Type 1 Autoimmune Pancreatitis

Abstract: Autoimmune pancreatitis (AIP) is a unique form of chronic pancreatitis characterized by high serum IgG4 concentration and a variety of complicating extra-pancreatic lesions. In particular, lachrymal/salivary gland lesions tend to manifest in a highly active AIP disease state, and several genes are speculated to be associated with the onset of this complication. We therefore searched for candidate susceptibility genes related to lachrymal/salivary gland lesions in a genome-wide association study (GWAS) with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…(1) Genetic loci KLF7, FRMD4B, LOC101928923, MPPED2 in Japanese AIP associated with lacrimal/salivary gland lesions [14] Decreased MST 1 of regulatory T in Japanese AIP with extra-pancreatic lesions [17] FGFBP2 (fibroblast growth factor binding protein type 2): single base deletion in IgG4-RD [19] (2) Persistent exposure of intestinal commensal flora antigen in mouse AIP model Avirulent E. coli (as PAMP activator) induces anti-CA II, anti-LF and ANA in mouse AIP with salivary gland involvement [20] Commensal E. coli-derived membrane protein flagellin (FliC) induces AIP-like inflammation in mouse model [21] Intestinal microflora can activate TLRs and NLRs on basophils to promote Th2 skewing and IgG4 production in the presence of BAFF [22][23][24][25][26] (3) Intestinal dysbiosis-mediated AIP development via pDC activation Decrease in gut Bacteroides, Streptococcus and Clostridium species in patients with AIP, compared to chronic pancreatitis [28] Activation of pDC by innate immune responses against intestinal dysbiosis in experimental mouse AIP [29] BAFF-B cell-activating factor of TNF family; pDC-plasmacytoid dendritic cell; CA-carbonic anhydrase; LF-lactoferrin; ANA-antinuclear antibodies.…”
Section: Intestinal Dysbiosis-mediated Aipmentioning
confidence: 99%
“…(1) Genetic loci KLF7, FRMD4B, LOC101928923, MPPED2 in Japanese AIP associated with lacrimal/salivary gland lesions [14] Decreased MST 1 of regulatory T in Japanese AIP with extra-pancreatic lesions [17] FGFBP2 (fibroblast growth factor binding protein type 2): single base deletion in IgG4-RD [19] (2) Persistent exposure of intestinal commensal flora antigen in mouse AIP model Avirulent E. coli (as PAMP activator) induces anti-CA II, anti-LF and ANA in mouse AIP with salivary gland involvement [20] Commensal E. coli-derived membrane protein flagellin (FliC) induces AIP-like inflammation in mouse model [21] Intestinal microflora can activate TLRs and NLRs on basophils to promote Th2 skewing and IgG4 production in the presence of BAFF [22][23][24][25][26] (3) Intestinal dysbiosis-mediated AIP development via pDC activation Decrease in gut Bacteroides, Streptococcus and Clostridium species in patients with AIP, compared to chronic pancreatitis [28] Activation of pDC by innate immune responses against intestinal dysbiosis in experimental mouse AIP [29] BAFF-B cell-activating factor of TNF family; pDC-plasmacytoid dendritic cell; CA-carbonic anhydrase; LF-lactoferrin; ANA-antinuclear antibodies.…”
Section: Intestinal Dysbiosis-mediated Aipmentioning
confidence: 99%
“…In contrast, our study used high-throughput sequencing. A recent genome-wide association study did not reveal the genes that are associated with AIP susceptibility [11] . The present study is therefore the first comprehensive analysis of the genes related to AIP susceptibility.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we also explored the genes that were associated with susceptibility to extra-pancreatic lesions, including sclerosing cholangititis, sialadenitis, dacryoadenitis, interstitial nephritis and lymph node swelling, and identified two candidates. Oguchi et al performed a genome-wide association study and extracted ten candidates associated with susceptibility to dacryoadenitis or sialadenitis in the Japanese patients with AIP, while no genes associated with all extra-pancreatic lesions was identified [11] . In this study, because sialadenitis and dacryoadenitis were only observed in two and three patients, respectively, we could not identified the genes that were specifically associated with dacryoadenitis or sialadenitis susceptibility in AIP patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein encoded by the FRMD4B ( GRSP1 ) gene is a GRP1‐binding protein, which may act as a scaffolding protein, as it contains both two coiled coil domains and a FERM protein interaction domain 43 . Association of FRMD4B genetic variants had been reported in GWAS of advanced heart failure, 44 coeliac disease 45 and type 1 autoimmune pancreatitis 46 . Interestingly, GWAS of thiopurine metabolism in UK ALL97 patients identified an association with FRMD4B genetic variants 47 .…”
Section: Discussionmentioning
confidence: 99%